Analisis Pembelajaran Berbasis Proyek Untuk Menguatkan Literasi Membaca dan Menulis Siswa Kelas 3 SD Muhammadiyah 1 Lamongan - Zurifa Nur Widyanti; Afriska Anggi Putri Vianto; Windah Septi Ashari; Abdul Muiz; Rizka Novi Irmaningrum (Primera Educatia Mandalika: Elementary Education Journal, 2026)
This study examines the implementation of Project-Based Learning (PBL) as an effort to enhance reading and writing literacy skills of 3 students at SD Muhammadiyah 1 Lamongan. The study was motivated by the insufficient level of students’ literacy skills, particularly in reading comprehension and written communication. A qualitative approach with a descriptive research design was employed. The research participants consisted of 3b students and the classroom teacher. Data were gathered through classroom observations, interviews, and document analysis. The research process involved project planning, implementation of project-based learning activities, and assessment of students’ learning outcomes. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the application of Project-Based Learning increases students’ engagement in reading and writing activities. Students demonstrated greater interest in reading various texts and improved ability to express ideas in written form. Moreover, Project-Based Learning supports the development of students’ critical thinking skills, collaboration, and responsibility. Thus, Project-Based Learning is considered an effective instructional approach for strengthening reading and writing literacy among elementary school students.